A importância do acolhimento escolar para pais de crianças autistas - ARIAS, Ariela Thayná de Souza (2019)
This work are come on studied about the welcoming approachment in environment school, using two families with autism children. That aims to understand the welcoming approachment, the effects in the family lifes, and autism children; to describe how the welcoming of process parents of autism children in the educational institutions, and to identify the possibilities that the school to promote, the inviting process, the parents and children with autism in the teaching and learning process. The theoretical research for to realize and comprehend this work is based in Vygotski (1991), Aranha (2001), Glat and Fernades (2005), Mantoan (2003), Davim (2017), Chizzoti (1991), Padua (2000), and Freire (1987). The research is coming the two studies based in the GIl (2008) conception, Using two families with autism children and the coordinator of the regular school that one them studies. The information production occurred through the bibliographical survey the main concepts that are reflected in this study, after that, the interviews were conducted in search of a better approximation of the theory with daily experience of autism children. The results this research report that autism is still a little known disorder, and the difficulties for to understand begins in late diagnosis and this affects the effective educational development of the children with ASD (Autism Spectrum Disorder). Although the society reflect about to work inclusive pedagogical practices, this reality is still quite compromised within the educational institutions it is perceived that the welcoming is little known in environment educational, but that are execution a necessary practice, which enables the acceptance of the person with this disorder in the family and it can reduce the impact of discovery of the disorder in the family. However, that implantation of the welcoming is still a reality unthought within the educational environment, the implantation can bring improvements to inclusion of people with disorder and help in the partnership between family and school.